2011
DOI: 10.3892/ijmm.2011.602
|View full text |Cite
|
Sign up to set email alerts
|

Role of tumor necrosis factor-α in the pathogenesis of indomethacin-induced small intestinal injury in mice

Abstract: Abstract. The pathogenesis of small intestinal damage caused by non-steroidal anti-inflammatory drugs (NSAIDs) such as indomethacin is still unclear. For this reason, there is currently no therapeutic strategy for ameliorating such damage. On the other hand, molecular treatment strategies targeting tumor necrosis factor (TNF)-α exert beneficial effects on intestinal lesions in patients with inflammatory bowel disease (IBD). To clarify the participation of TNF-α in NSAID-induced small intestinal damage, we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…Specifically, NSAID-induced small intestinal and gastric ulcers were reduced by a TNF-α synthesis inhibitor [54, 55]. Similarly, indomethacin-induced inflammatory bowel disease was alleviated by the antibody to TNF-α or gene deletion of TNF-α [56, 8]. TNF-α mediated ulceration involves apoptosis [57].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, NSAID-induced small intestinal and gastric ulcers were reduced by a TNF-α synthesis inhibitor [54, 55]. Similarly, indomethacin-induced inflammatory bowel disease was alleviated by the antibody to TNF-α or gene deletion of TNF-α [56, 8]. TNF-α mediated ulceration involves apoptosis [57].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to PGE 2 , multiple other biological pathways seem responsible for the formation of NSAID-induced ulcers [711]. While NSAIDs suppress inflammation, NSAID-induced ulcers are associated with increases in the levels of inflammatory markers such as TNF-α and IL-6 [8, 12]. Although a downstream consequence of COX-2 activity, TNF-α is proposed to play an important role in ulcer pathways activated by prolonged use of NSAID.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the toxicopathology studies, 5–11 mice per treatment group were used, and for the kinetic study, nine mice per treatment group (three mice for identical time points). The doses for the three NSAIDs (DCF, 60 mg/kg; indomethacin, 10 mg/kg; ketoprofen, 100 mg/kg) were selected from previously published studies (Fukumoto et al, 2011; Ramirez-Alcantara et al, 2009); after correction with the interspecies dose scaling factor (× 12 for mouse) (Kirman et al, 2005), they are comparable to the human therapeutic doses. The intraperitoneal route was selected to ensure maximal absorption and to minimize drug–drug interactions during administration; previous data have shown that DCF administered either intraperitoneally or orally produced a similar extent of enteropathy in rats, due to the critical role of hepatobiliary excretion of glucuronoconjugates (Seitz & Boelsterli, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…A major proinflammatory cytokine that increases via TLR4 signaling following indomethacin treatment is tumor necrosis factor-α (TNF-α) (144). The causal involvement of TNF-α in the development of enteropathy has been convincingly demonstrated with anti-TNF-α antibodies or TNF-α-null mice, as both types of mice are protected against indomethacin-induced injury (145, 146). Similarly, intraperitoneal administration of antineutrophil antibody attenuates indomethacin-induced enteropathy (147), providing evidence for a causal role of PMNs in the pathogenesis of NSAID enteropathy.…”
Section: Bacterial Molecules and Nonsteroidal Anti-inflammatory Drug mentioning
confidence: 98%